EFEKTIFITAS GAYA KEPEMIMPINAN DALAM MEMANAJEMEN RODA PEMERINTAHAN MASYARAKAT DESA TORJUNAN KABUPATEN SAMPANG - Ajisaputra, Arnanda (Journal of Innovation in Business and Economics, 2014)
The research objective was to clarify the effectiveness of leadership style of Torjunan  headman in terms of bureaucratic leadership that leads to its function as part of the Indonesian government institutions at the village level, and in terms of Situational Leadership leading to its function as the leader and protector of society. The instruments used in data collection were interviews, observation, and documentation; which further examined using three methods of data analysis namely; Miles analysis, which covered: data collection, data reduction, data presentation, and conclusion; Reddin analysis consisting of synchronization, data input, as well as the calculation of the average; and Hersey and Blanchard analysis comprising: synchronization, data input and drawing conclusions based on the accumulative column. The results showed: 1) Torjunan headman was seem less flexible in terms of managing the issues related to government affairs, especially regarding the bureaucratization of Robatal sub-district; 2) based on Blanchard Situational Leadership II model, Torjunan headman style were classified into G4 category, which means that Torjunan headman would be able to work more effective if he delegated the decision-making, as well execution, to society